Polyglactin 910 Meshes Coated with Sustained-Release Cannabigerol Varnish Inhibit Staphylococcus aureus Biofilm Formation and Macrophage Cytokine Secretion: An In Vitro Study - Mustafa Abudalu; Muna Aqawi; Ronit Vogt Sionov; Michael Friedman; Irith Gati; Yaron Munz; Gil Ohana; Doron Steinberg (MDPI AG, 2023)
Synthetic surgical meshes are commonly used in abdominal wall reconstruction surgeries to strengthen a weak abdominal wall. Common mesh-related complications include local infection and inflammatory processes. Because cannabigerol (CBG) has both antibacterial and anti-inflammatory properties, we proposed that coating VICRYL (polyglactin 910) mesh with a sustained-release varnish (SRV) containing CBG would prevent these complications. We used an in vitro infection model with Staphylococcus aureus and an in vitro inflammation model of lipopolysaccharide (LPS)-stimulated macrophages. Meshes coated with either SRV-placebo or SRV-CBG were exposed daily to S. aureus in tryptic soy medium (TSB) or macrophage Dulbecco's modified eagle medium (DMEM). Bacterial growth and biofilm formation in the environment and on the meshes were assessed by changes in optical density, bacterial ATP content, metabolic activity, crystal violet staining, spinning disk confocal microscopy (SDCM), and high-resolution scanning electron microscopy (HR-SEM). The anti-inflammatory effect of the culture medium that was exposed daily to the coated meshes was analyzed by measuring the release of the cytokines IL-6 and IL-10 from LPS-stimulated RAW 264.7 macrophages with appropriate ELISA kits. Additionally, a cytotoxicity assay was performed on Vero epithelial cell lines. We observed that compared with SRV-placebo, the segments coated with SRV-CBG inhibited the bacterial growth of S. aureus in the mesh environment for 9 days by 86 ± 4% and prevented biofilm formation and metabolic activity in the surroundings for 9 days, with respective 70 ± 2% and 95 ± 0.2% reductions. The culture medium that was incubated with the SRV-CBG-coated mesh inhibited LPS-induced secretion of IL-6 and IL-10 from the RAW 264.7 macrophages for up to 6 days without affecting macrophage viability. A partial anti-inflammatory effect was also observed with SRV-placebo. The conditioned culture medium was not toxic to Vero epithelial cells, which had an IC50 of 25 µg/mL for CBG. In conclusion, our data indicate a potential role of coating VICRYL mesh with SRV-CBG in preventing infection and inflammation in the initial period after surgery.